Agricultural digital twins. (13th July 2022) - Zhao, Yuhang; Jiang, Zheyu; Qiao, Liang; Guo, Jinkang; Pang, Shanchen; Lv, Zhihan
In recent years, the development of digital twins has advanced by leaps and bounds, and digital twins have gradually begun to combine various fields and apply them to the current digitalisation of the physical world. Digital twins can play an important role in the field of agriculture. Digital twins technology can fully improve the yield and profit of crop products and alleviate food safety issues. Regarding the current common problems in the agricultural field, this article synthesises the existing technologies of digital twins, discusses the development prospects of it in the agricultural field, and puts forward the problems that still exist in the application of digital twins in the agricultural field.